2014
DOI: 10.4161/rna.29143
|View full text |Cite
|
Sign up to set email alerts
|

Two splicing factors carrying serine-arginine motifs, TSR1 and TSR1IP, regulate splicing, mRNA stability, and rRNA processing inTrypanosoma brucei

Abstract: In trypanosomes, mRNas are processed by trans-splicing; in this process, a common exon, the spliced leader, is added to all mRNas from a small RNa donor, the spliced leader RNa (sL RNa). however, little is known regarding how this process is regulated. In this study, we investigated the function of two serine-arginine-rich proteins, TsR1 and TsR1IP, implicated in trans-splicing in Trypanosoma brucei. Depletion of these factors by RNai suggested their role in both cisand trans-splicing. Microarray was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 92 publications
(121 reference statements)
1
40
0
Order By: Relevance
“…Data from Manger and Boothroyd ( 38 ) and our analysis (data not shown) indicated that TbRRM1 does not play a global role in trans -splicing. However, given its association with PTB2, we cannot exclude that TbRRM1 functions in splicing commitment for a subset of transcripts, analogous to some SR splicing factors in mammals and TSR1 in T. brucei ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Manger and Boothroyd ( 38 ) and our analysis (data not shown) indicated that TbRRM1 does not play a global role in trans -splicing. However, given its association with PTB2, we cannot exclude that TbRRM1 functions in splicing commitment for a subset of transcripts, analogous to some SR splicing factors in mammals and TSR1 in T. brucei ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“… T. brucei possesses at least two SR proteins, TbRRM1 (Tb927.2.4710) and TSR1 (Tb927.8.900), which were identified independently ( 34 , 35 ). TSR1 has recently been shown to modulate the splicing of a subset of transcripts and is considered an auxiliary factor in this process ( 36 ). In addition, three more SR proteins are predicted to be encoded in the genome (RBSR1 [Tb927.9.6870], RBSR2 [Tb927.7.1390], and RBSR3 [Tb927.3.5460]).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this arrangement, regulation of gene expression in trypanosomes is almost exclusively post-transcriptional: there are big differences between mRNAs in their processing efficiencies, decay rates, and translation (47)(48)(49). RNA-binding proteins have been shown to regulate specific trypanosome mRNA subsets, acting on splicing, mRNA decay, and / or translation (50)(51)(52). With one exception, however (53), the molecular mechanisms by which these proteins act are not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Several SR proteins exist in T. brucei, among them: TSR1 (Ismaili et al 1999) and TSR1IP (Ismaili et al 2000), and one SR-related protein, TbRRM1 (RNA-binding protein RRM1) (Manger and Boothroyd 1998). TSR1 and TSR1IP have been shown to be involved in cis and trans-splicing, as well as in the regulation of mRNA stability of a subset of transcripts and in rRNA processing (Gupta et al 2014). Recently, it has been shown that TbRRM1 is involved in cell cycle regulation (Levy et al 2015), and both chromatin structure and transcriptome modulation (Naguleswaran et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…TSR1 and TSR1IP have been shown to be involved in cis and trans ‐splicing, as well as in the regulation of mRNA stability of a subset of transcripts and in rRNA processing (Gupta et al. ). Recently, it has been shown that TbRRM1 is involved in cell cycle regulation (Levy et al.…”
mentioning
confidence: 99%